Emergence of heavy tails in streamflow distributions: the role of spatial rainfall variability. (January 2023) - Wang, H.-J.; Merz, R.; Yang, S.; Tarasova, L.; Basso, S.
Highlights: Increasing spatial variability of rainfall determines heavier streamflow tails only beyond a certain increase threshold. Small and elongated catchments are less resilient to increasing spatial variability of rainfall. Daily records of rainfall and streamflow for a large set of catchments in Germany confirm simulations. Abstract: Flow events with low frequency often cause severe damage, especially if their magnitudes are higher than suggested by historical observations. The heavier right tail of streamflow distribution indicates the increasing probability of high flows. In this paper, we investigate the role played by spatially variable rainfall in enhancing the tail heaviness of streamflow distributions. We synthetically generated a wide range of spatially variable rainfall inputs and fed them to a continuous probabilistic model of the catchment water transport to simulate streamflow in five German catchments with distinct properties in size and topography. Meanwhile, we used a comparable approach to analyze rainfall and runoff records from 175 German catchments. We identified the effects of spatially variable rainfall on the tails of streamflow distributions from both simulation scenarios and data analyses. Our results show that the tail of streamflow distribution becomes heavier with increasing spatial rainfall variability only beyond a certain threshold. This finding indicates the capability of catchments to buffer growing heterogeneities of rainfall, which we term catchment resilience to increasing spatial rainfall variability. The analyses suggest that the runoff routing through the river network controls this property. In fact, both small and elongated catchments are less resilient to increasing spatial rainfall variability due to their intrinsic runoff routing characteristics. We show the links between spatial rainfall characteristics and catchment geometry and the possible occurrence of high flows. The data analyses we performed on a large set of case studies confirm the simulation results and provide confidence for the transferability of these findings.